Evaluation of tomato yield using statistical tests - Moigradean Diana (Proceedings of the International Symposium on Analytical and Environmental Problems, 2015)
The main objective of this study is to calculate the correlation existed between the NPK mineral fertilization doses on tomato yield using statistical tests (multiple regression analysis of variance, the F-test, value of R and R2 , Durbin–Watson test). A field experiment was using two tomatoes samples in different precocity steady (Export II and Ace Royal) cultivated in Romanian west area. Multiple regression analysis of variance on the influence of fertilization on the yield of Export II cultivar show that 90.28% of the production variability is due to the influence of these three macronutrients (NPK) while the yield of Ace Royal cultivar the percentage is 97.78%. The tomato yield increases with the fertilization doses and nitrogen fertilization has a major influence distinctly significant on achieving production, while the fertilization with potassium is lower but superior to phosphorus fertilization for two tomato cultivar.